Poly(furfuryl alcohol)-assisted pyrolysis synthesis of ceramic nanoparticles for solid oxide fuel cells - Dong, Dehua; Yao, J.; Li, Chun-Zhu; Wang, H. (Pergamon, 2012)
A pyrolysis synthesis method was developed to prepare ceramic nanoparticles for the fabrication of solid oxide fuel cells. Furfuryl alcohol was used as a polymerizable solvent to dissolve metal nitrates and then polymerized into poly(furfuryl alcohol) (PFA). During the pyrolysis at 600 °C, a mixture of nitrates/PFA was converted into ceramic nanoparticles/carbon networks nanocomposite, and the carbon networks act as a barrier to prevent the aggregation of newly formed nanoparticles during particle crystallization. Dispersible nanoparticles with particle sizes ranging from 40 nm to 200 nm were obtained after burning off carbon networks in air. As an example, Ce0.8Sm0.2O1.9 nanoparticles were synthesized to prepare solid oxide fuel cells, and the fuel cells achieved maximum power densities of 444.5, 625.5 and 684 mW cm−2 at 500 °C, 550 °C and 600 °C, respectively. Our study shows that the pyrolysis synthesis method described here is promising for the effective synthesis of high quality ceramic nanoparticles.